The Role of the Madrasah Principal in Managing Education in the Digital Age - Imailda Nur Laila; Muhamad Taufik Bintang Kejora; Wahidin Wahidin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Advances in digital technology have brought significant changes to the education system, including in madrasahs. This article aims to examine the role of madrasah principals in managing education in the digital age, covering aspects of leadership, management, teacher competency development, learning innovation, as well as the challenges and strategies faced. The method used is a literature review with a qualitative approach through content analysis of various sources. The results of the study indicate that madrasah principals serve as visionary and transformational leaders in integrating technology, enhancing teacher competencies through training and supervision, and promoting digital learning innovations such as e-learning and blended learning. However, implementation still faces obstacles such as limited infrastructure, low digital literacy, and resistance to change. Therefore, strategies are needed through the strengthening of human resources, the provision of facilities and infrastructure, as well as the development of an adaptive digital culture grounded in Islamic values.